Peran Guru dalam Pelaksanaan Budaya Sekolah 5S (Senyum, Salam, Sapa, Sopan, Santun) untuk Membentuk Akhlakul Karimah Siswa (Studi Kasus di MTs. Madrasatul Qur'an Tebuireng Jombang) - Amiroh, Kharisma; Arini, Aida (Al Tadib : Jurnal Ilmu Pendidikan, 2023)
This artikel describes the implementation of school culture 5S. With the teacher’s role in implementing the 5S school culture, it is hoped that it can form studens akhlakul karimah. Researchers use a qualitative approach to explain something in depth, using a type of case study research. Data collection methods used are observation, interviews, documentation.. The results of the study show that the implementation of the 5S shool culture in MTs. Madrasatul Qur’an madasah activities, spontaneous, and conditioning. In implementing the 5S school culture the teacher has a role as a role model and guide so that it can form students akhlakul karimah. The supporting factors are a condusive madrasah environment, adequate infrastructure, good cooperation between madrasah and islamic boarding schools, competent teacher’s and the majority of Al-Qur’an memorizers. While the inhibiting factors is that students are hetereneous who are not used to it with the culture that exists in madrasah, the influence of friends, and the lack of awareness of student’s in implementing school culture 5S.